Tim-3 Promotes Listeria monocytogenes Immune Evasion by Suppressing Major Histocompatibility Complex Class I. (5th October 2019) - Wang, Zhiding; Li, Ge; Dou, Shuaijie; Zhang, Yanling; Liu, Yiqiong; Zhang, Jiacheng; Li, Guoxian; Hou, Chunmei; Wang, Renxi; Shen, Beifen; Han, Gencheng
Abstract: Background: T-cell immunoglobulin and mucin protein 3 (Tim-3) is an immune checkpoint inhibitor that has therapeutic implications for many tumors and infectious diseases. However, the mechanisms by which Tim-3 promotes immune evasion remain unclear. Methods: In this study, we demonstrated that Tim-3 inhibits the expression of major histocompatibility complex class I (MHC-I) in macrophages at both the messenger ribonucleic acid and protein levels by inhibiting the STAT1-NLRC5 signaling pathway. Results: As a result, MHC-I-restricted antigen presentation by macrophages was inhibited by Tim-3 both in vitro and in a Listeria monocytogenes infection model in vivo. Systemic overexpression of Tim-3 or specific knockout of Tim-3 in macrophages significantly attenuated or enhanced CD8 + T-cell activation and infection damage in L monocytogenes -infected mice, respectively. Conclusions: Thus, we identified a new mechanism by which Tim-3 promotes L monocytogenes immune evasion. Further studies on this pathway might shed new light on the physio-pathological roles of Tim-3 and suggest new approaches for intervention. Abstract : Tim-3 inhibits the expression of MHC-I on macrophages via STAT1/NLRC5 signaling pathway. As a result, Tim-3 inhibits MHC-I-mediated antigen presentation by macrophages, which then attenuates adaptive immunity and enhances Listeria monocytogenes immune evasion.